2022
DOI: 10.1186/s12891-022-06010-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical outcomes between vascularized bone graft and the Masquelet technique for the reconstruction of Gustilo type III open tibial fractures

Abstract: Background Gustilo type III tibial fractures commonly involve extensive soft tissue and bony defects, requiring complex reconstructive operations. Although several methods have been proposed, no research has elucidated the efficacies and differences between vascular bone graft (VBG) and the Masquelet technique (MT) to date. We aimed to evaluate and compare the clinical effectiveness of VBG and the MT for the reconstruction of Gustilo type III tibial fractures. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Wang et al’s study revealed a mean union time of 6.1 months (range, 5 to 8 months) [ 9 ]. However, despite an even shorter average length of bone loss (5.3 and 5.1 cm), a much longer mean union time was indicated in the investigations of Zoller et al and Lan et al investigations (17.2 and 15.1 months, respectively) [ 15 , 16 ]. In our current study, the union time of the fracture falls between the two groups, with an average union time of 12.2 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al’s study revealed a mean union time of 6.1 months (range, 5 to 8 months) [ 9 ]. However, despite an even shorter average length of bone loss (5.3 and 5.1 cm), a much longer mean union time was indicated in the investigations of Zoller et al and Lan et al investigations (17.2 and 15.1 months, respectively) [ 15 , 16 ]. In our current study, the union time of the fracture falls between the two groups, with an average union time of 12.2 months.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the findings of Masquelet, who reported that bone union time is not dependent on the length of bone loss [ 17 , 18 ]. Notably, there was only one postoperative superficial infection in Kang’s study and two postoperative superficial infections in Wang’s study, whereas postoperative infections in Zoller and Lan’s study were associated with a high occurrence of postoperative osteomyelitis which suggested that a sterile surgical environment is a significant contributing factor to prolonged union time [ 15 , 16 ]. However, in our study, the bone union time was relatively longer than that in Wang’s investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are not many direct comparative studies, some have shown similar outcomes when comparing vascularized bone grafting to the induced membrane and distraction osteogenesis techniques. 29 , 30 …”
Section: Techniquesmentioning
confidence: 99%
“…The various technical modalities for bone defect reconstruction, including bone grafting, temporary spacers and staged Masquelet technique, distraction osteogenesis, and vascularized bone transfer, are beyond the scope of this review article and covered elsewhere in the literature. [63][64][65] A case example of a patient with an infected nonunion from a high-energy open humerus shaft fracture managed by free microvascular fibular bone transfer is shown in Figure 3. New innovative modalities aimed at by The IIIB open tibia shaft fracture was managed by surgical debridement and temporizing spanning external fixation (A).…”
Section: Timing Of Surgical Debridementmentioning
confidence: 99%